Static Analysis of Electric Vehicle Prototype Frame - Ramadhoni, Tri Satya; Rifa'i, Ahmad Imam; Anwar, Zainuri; Hidayati, Baiti; Sumarna, Herlin; Okviyanto, Toni; Sampurno, Rachmat Dwi (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
This study aims to determine the strength of the prototype car frame created by the SMES (Sriwijaya Mechanical Engineering Squad) team in participating in the KMHE (Energy Efficient Car Contest) and SEM (Shell Eco-Marathon). This prototype vehicle is an energy-efficient car with an electric motor drive and utilizes a hollow rectangular tube-shaped frame with aluminum 6061 material. The overall dimensions of the car frame are 2500x410x540 mm. Static loading analysis was conducted using manual calculations and computer simulations. Static loading was performed on seven support bars, the main bar, and the overall prototype car frame. Applied loads include the electric motor load, control panel, battery load, driver's body load, driver's legs, front body load, rollbar body load, rear body load, and reaction loads from bars receiving direct loads. Autodesk Inventor software with frame analysis features was used in the simulation process. Based on the results of manual calculations and computer simulations, the difference in the average results of maximum bending moment, maximum stress, and displacement on the seven types of support bars, with a small error tolerance below 10%, is 1.01%, 5.24%, and 3.25%, respectively. Based on computer simulation results for the main bar and seven types of support bars, the highest maximum stress occurs in the main bar, which is 128727.37 N.